Keterampilan Kerajinan Tali Kur Kepada Remaja sebagai Bekal Wirausaha - Triehierdawati Triehierdawati; Siswoyo Siswoyo; Syilvia Wenny (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
This community service program aims to transfer skills in making kur rope crafts to teenagers as a foundation for entrepreneurship and life skills development. The program targets youth groups in the community who lack optimal productive skills. Methods used include counseling, hands-on training, mentoring, and product evaluation. The results of the program indicate that participants are able to understand basic and advanced techniques for making kur rope crafts such as key chains, bracelets, and simple bags. Furthermore, participants demonstrated increased interest in entrepreneurship and creativity in product development. This activity is expected to be an alternative solution for empowering teenagers to become more economically and creatively independent.